Fish Stock Status Assessment in Alue Naga Waters Using A 200 Khz Single Beam Echosounder - Syahrul Purnawan; Sofyatuddin Karina; Myounghee Kang; Henry Manik (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2023)
Monitoring fish stocks is an important part of sustainable management of fisheries resources. Conducting the current evaluation is very difficult since there are no reliable data on the potential for fisheries in the waters surrounding Banda Aceh city. The hydroacoustic method was used for the first time in the waters of Alue Naga, located north of Banda Aceh, to evaluate the condition of fish stocks. A single beam scientific echosounder with a frequency of 200 kHz was used to collect hydroacoustic data in the area. The collected data was then processed using the Sonar5-Pro software. Cell integration was carried out at an interval of 10 meters vertically with an elementary sampling distance (ESD) of 200 m. While the volume backscattering strength (SV) value tends to be the highest in intermediate layers, the target strength (TS) value was found to be maximum in deeper layer, reaching a maximum value of -49.46 dB at a depth of 51–60 m. Area density value (#.ha-1) was found to be the highest at a depth of 11-20 m, while Biomass (g.ha-1) at a depth of 21-30 m was the highest among other depth layers with a value of 1558 g.ha-1. According to the in-situ catches of Carangoides, Selaroides, Aphareus, Variola, and Priacanthidae, there are a number of potential reef fish resources in the waters of Alue Naga. The findings of this study strongly support the conclusion that the hydroacoustic method effectively provides comprehensive information on the horizontal and vertical distribution of fish in Alue Naga waters.